PERANGKAT LUNAK KRIPTOGRAFI FILE TEKS MENJADI BENTUK CITRA DIGITAL MENGGUNAKAN METODE KERBEROS - Damanik, Romanus (UNIVERSITAS PELITA HARAPAN, 2017)
Rapid development of current computer technology often lead to abuse of the technology in a criminal action. One of the most common is the theft of the Password (password), personal accounts until confidential documents. To that end, the perceived need for a form of safeguard against the things above in order to comfort the user in using computer technology. Encryption is one method to randomize the words so that it cannot be read and understood by anyone else except by users who use them and those who were given the right to use it. The Kerberos method is a method of encryption that originally applied to secure a computer network. Kerberos authentication works by comparing input data with the given keywords. Based on the workings of the Kerberos method, be designed a device for data security in the form of a text message is converted into the form of a digital image. Through the processing of Binary value from the message text inputed. will be generated a digital image is the result of a binary-binary encryption of text messages through the Kerberos method. This type of data security is more secure than cryptography that produce the same output with the Plaintext, such as cryptographic text messages that generate output in the form of a digital berbedayaitucitra denganbentuk message.Keywords: Â Cryptography, Kerberos, Conversion, Digital Image